Childhood ovarian neoplasms in Ibadan, South‑western Nigeria. (2016)
Childhood ovarian neoplasms are very rare. Little information is available on the relative pattern and frequency of these tumors in Nigerian children. Earlier study done in Ibadan involved ovarian neoplasms in children and adolescents. The aim of this study is to review cases of ovarian neoplasms in childrenMaterials and Methods: This was a retrospective study. Twenty four cases of childhood ovarian neoplasms were seen in patientsResults: Childhood ovarian neoplasms accounted for 2.8% of all cases of ovarian tumors seen in this period. Fourteen (58.3%) cases of childhood ovarian neoplasms were benign, and 10 (41.7%) were malignant. Mature cystic teratoma occurring in 13 (54.2%) was the most common childhood ovarian neoplasm and was most prevalent between 10 and 14 years of age. Burkitt lymphoma was the most common 4 (40%) malignant childhood ovarian tumor and prevalent between 5 and 14 years of age. Conclusion: Mature cystic teratoma remains the single most common childhood ovarian neoplasms, and Burkitt’s lymphoma is the most malignant childhood ovarian tumor in Ibadan, South western Nigeria.